(untitled) (CIPEEX, 2023)
The present work addresses the categorization of organic impurities in medications, as well as discusses the identification, isolation, and characterization of unknown degradation products observed during stability and forced degradation studies. The entire approach aims at defining an appropriate specification and analyzing the impurity, enabling a comprehensive understanding of the product, which is an indispensable object during the registration process with the National Health Surveillance Agency (ANVISA). In light of this, this study is the result of technical-scientific cooperation between the productive sector and academia, in the search to identify, isolate, and characterize an unknown impurity found in one of the proton pump inhibitor medications from a pharmaceutical industry.